Torque in Orthodontics - -, Deepshikha; Chaukse, Ankur; Gupta, Kshitij; Soni, Mayur; Patil, Gourav; Singhai, Abhideep (Journal of Orofacial Research, 2020)
Torque is a shear-based moment, a force obtained from a twisted spring wire in its effort to un-twist itself which causes rotation. In dentition, it pertains to facio-lingual root movement and control. Also, it refers to the amount of twist applied to an arch wire in bracket engagement or activation. Despite the advent of numerous treatment philosophies, appliance systems and torque prescriptions and considerable research done in the past, torque is still an enigma. The key is to understand not only how we reach where we are but also to learn how to manage the torque properly, focusing on the technical and biomechanical purposes that led to the change of the torque values over time. The present review focuses on application of torque in orthodontics.